IMPLEMENTASI SURAT EDARAN KEPALA DINAS PENDIDIKAN KABUPATEN BLORA NOMOR 443.2/ 1156 TAHUN 2020 TENTANG LAYANAN PENYELENGGARAAN PENDIDIKAN DALAM RANGKA PENCEGAHAN PENULARAN DAN PENYEBARAN INFEKSI CORONA VIRUS DISEASE-19 DI JAWA TENGAH PADA SMP NEGERI 2 JEPON - Suparjo . (JI@P, 2022)
The implementation circular letter from the head of the Blora district office regarding Education Delivery Services in the Context of Preventing theTransmission and Spread of Corona Virus Disease (Covid-19) infection in CentralJava at SMP N 2 Jepon. The results of the study indicate that there iscommunication, resources, disposition and bureaucratic structure in implementingcircular letter from the head of the Blora district office regarding EducationDelivery Services in the Context of Preventing the Transmission and Spread ofCorona disease (COVID-19) infection in Central Java at SMP N 2 Jepon throughlong distance learning. In learning activities there are several obstacles, includinggeographical location, costs, infrastructure, bored students and the characteristicsof students who are more interested in playing games. The school has madeimprovements in learning through socialization, interesting learning, internetquotas for learning and providing learning motivation. The conclusion of theimplementation of the circular letter of the Head of the Blora Regency EducationOffice Number 443.2/1156 of 2020 at SMP Negeri 2 has not run optimally, becausethere are still some children's rights that are not fulfilled.Keywords: Communication, resources, disposition and bureaucratic structure